Scalable total synthesis of natural vanillin-derived glucoside ω-esters - Avetyan (Avetian) D. L. David Ludvigovich; Shatskiy A. Andrey; Karkas M. D. Markus; Stepanova E. V. Elena Vladimirovna (2022, 2022)
Title screen